Trabalho e atividade na psicologia de A. N. Leotiev: pressupostos ontológicos e contribuições ao processo educativo/formativo da classe trabalhadora - Cabó, Leonardo José Freire (2012)
This research adopted as the object of study the relationship between work and activity in the psychology of A. N. Leontiev. Theoretical and literature, our study aimed at investigating the foundations and structure of the "activity theory", developed initially by Vygotsky and Leontiev and systematized by which, nowadays, is taken up by scholars from various fields of humanities, peering, and specifically its relationship with work in Marx (1984, 2004, 2005) and Lukacs (1978, 1981) and their contributions to the project educational / training in contemporary working class. To achieve the proposed objectives, dwelt us about some of the major works of Leontiev (1978a, 1978b, 1980, 1988, 1999) as well as texts / books published by Vygotsky (1988, 1995, 1999, 2000, 2004), Luria (1979, 1988a; 1992), Elkonin (1987, 1988), Davydov (1988) and Shuare (1990), as well as interpreters of Brazilian research on elaborations of Historical-Cultural Psychology, especially the construct of theoretical and practical Leontiev, like Duarte (2004, 2001), Tuleski (2007, 2009), Do Carmo (2008), Barroco (2007a, 2007b), Pasqualini (2006, 2010), Asbarh (2005, 2011), Gonçalves (2005) among others. At the end, we establish general traits that comprise what the author calls "dominant activity," his contributions to the development process of the psyche of the child and the educational process/formation of the working class on the threshold of the XXI century.